1998
DOI: 10.1182/blood.v92.7.2410
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline of Perforin Expression in Human Cytotoxic T Lymphocytes and Natural Killer Cells

Abstract: In this study a flow cytometric technique for detecting cytoplasmic perforin (P) has been used to quantify age-related changes in perforin expression in human peripheral blood lymphocytes (PBL). Proportions of P+ lymphocytes increased after birth, but declined rapidly after the age of 70 years. This was true for both T cells and CD16+ and CD56+ natural killer (NK) cells. Children showed in addition to high levels of perforin positive CD8+ cells a much higher proportion of CD4+P+ cells than the other age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Similar data for perforin expression were reported previously (Mariani et al. , 1996), although one group has reported reduced perforin expression with aging (Rukavina et al. , 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Similar data for perforin expression were reported previously (Mariani et al. , 1996), although one group has reported reduced perforin expression with aging (Rukavina et al. , 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Patients infected with HIV or hepatitis B virus (HBV) typically show a massive decrease in lymphocyte glutathione levels and a massive loss of natural killer (NK) cell activity and other immune functions (Eck et al 1989;Ullum et al 1995;Watanabe et al 2000;Azzoni et al 2002). It has also been shown that the absolute number of NK cells and the NK cell activity per cell decreases with age (Rukavina et al 1998). NK cells play an important role in the protection against viral or bacterial infections (Bukowski et al 1985;Rager-Zisman et al 1987;Scalzo 2002;Vankayalapati et al 2004;Warfield et al 2004), and in the suppression of tumours (Kim et al 2000;Tahir et al 2001).…”
Section: (G) Immune Functionsmentioning
confidence: 99%
“…Most studies have reported increased percentages of NK cells within blood mononuclear cells (BMNC) 32 , 33 , 34 and increased or unaltered concentrations in the blood 32 , 34 . Furthermore, there is a general consensus that NK cells from elderly humans show decreased cytotoxic capacity on a ‘per cell’ basis 35 , 36 . It has been suggested that increased concentrations of NK cells in the blood compensate for the decreased cytotoxicity per NK cell 7 .…”
Section: Ageing and Immune Functionmentioning
confidence: 99%